(3TQM aUjM KYdHs - (3CHh GdYHGS CMeO Hf jMji Hf RjO KYdH GdTjHGfj Gdchaj GdfMhj,J (B291 (3g` s
(3ChdgG (B:s
(3gPG MGVQgG (B: (3JfHjg , hPG (B: (3GSe jTGQHg Edi TF s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B252s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B16 - (3U (B358 s
(3eUOQ GbJfGA GdCUd (B:s
(3eOjfI (B(557) s
Keywords: (3GddZIs